Pivško jygajo se 'guncajo se' (Petelinje) ali o nastanku slovenskega razmerja jugati : gugati - Furlan, Metka (Slavistična revija, 2010)
Since the Pivka dialect does not have second palatalization of velars, the verb jyugajo se 'they are swinging' (Petelinje), with its Slovene phonetic equivalents from Slovene gúgati se, is explained with dissimilation g : g --> o : g and the appearance of the prothetic -j.
Keywords: glagol; leksikologija; lexicology; palatalizacija; Petelinje; pivški govor; Slovene; Slovene dialects; slovenska narečja; slovenščina; verb